2007
DOI: 10.1177/0267658307076546
|View full text |Cite
|
Sign up to set email alerts
|

The Interpretability Hypothesis: evidence from wh-interrogatives in second language acquisition

Abstract: The second language acquisition (SLA) literature reports numerous studies of proficient second language (L2) speakers who diverge significantly from native speakers despite the evidence offered by the L2 input. Recent SLA theories have attempted to account for native speaker/non-native speaker (NS/NNS) divergence by arguing for the dissociation between syntactic knowledge and morpho(pho)nology. In particular, Lardiere (1998), Prévost and White (2000), and Goad and White (2004) claim that highly proficient lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
298
3
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 325 publications
(323 citation statements)
references
References 28 publications
18
298
3
4
Order By: Relevance
“…Examining Morphological Variability in L2 Learners 56 An additional question that we examined concerns the relation between the L2ers' knowledge of lexical gender and their ability to compute gender agreement in online comprehension and production, in order to better adjudicate between proposals which argue for a deficit at the level of syntactic agreement (e.g., Tsimpli and Dimitrakopoulou, 2007) and proposals which argue for problems at the level of lexical assignment and retrieval (Grüter et al, 2012;Hopp, 2013;Prévost and White, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Examining Morphological Variability in L2 Learners 56 An additional question that we examined concerns the relation between the L2ers' knowledge of lexical gender and their ability to compute gender agreement in online comprehension and production, in order to better adjudicate between proposals which argue for a deficit at the level of syntactic agreement (e.g., Tsimpli and Dimitrakopoulou, 2007) and proposals which argue for problems at the level of lexical assignment and retrieval (Grüter et al, 2012;Hopp, 2013;Prévost and White, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Under this account, it is in spoken production where L2ers might show reliance on default morphology and where variability with gender agreement is more likely to emerge, due to the burden associated with lexical retrieval (Grüter et al, 2012;Hopp, 2013). In contrast, representational accounts, such as the Interpretability Hypothesis (e.g., Tsimpli and Dimitrakopoulou, 2007) and McCarthy (2008), predict variability across the board (albeit for different reasons).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proposals claiming a deficit in knowledge for adult L2 learners have been formulated based on L2 learners' performance errors (e.g., Bley-Vroman, 1990;Clahsen & Muysken, 1986;Eubank, 1993Eubank, /1994Eubank, , 1994Hawkins & Chan, 1997;Hawkins & Hattori, 2006;Hawkins & Liszka, 2003;Tsimpli, 2003;Tsimpli & Dimitrakopoulou, 2007). This approach often links competence deficits with critical period effects reflecting learners' maturational changes, as, for instance, in a claim made by Beck (1999, p. 316): "The morphosyntactic features that require or prohibit thematic verb raising become impaired during the course of maturation."…”
mentioning
confidence: 99%
“…Relevant research in SLA has shown that, as regards formal grammatical properties and operations in the narrow syntax, near-native competence can be reached despite the fact that these are often underdetermined by input (Tsimpli et al, 2004;Lozano, 2006Lozano, , 2008Lozano, , 2016Sorace and Filiaci, 2006;Tsimpli and Sorace, 2006;Tsimpli and Dimitrakopoulou, 2007;Tsimpli and Mastropavlou, 2007;Sorace and Serratrice, 2009). 16 By contrast, syntactic focus movement involves operations not only in the narrow syntax but, crucially, at the syntax-discourse interface: in Greek syntactic focus movement involves an (interpretable)…”
mentioning
confidence: 99%